2017
DOI: 10.1126/science.aal5005
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric peptide pigments with sequence-encoded properties

Abstract: Melanins are a family of heterogeneous polymeric pigments that provide ultraviolet (UV) light protection, structural support, coloration, and free radical scavenging. Formed by oxidative oligomerization of catecholic small molecules, the physical properties of melanins are influenced by covalent and noncovalent disorder. We report the use of tyrosine-containing tripeptides as tunable precursors for polymeric pigments. In these structures, phenols are presented in a (supra-)molecular context dictated by the pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
258
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 264 publications
(264 citation statements)
references
References 31 publications
5
258
0
1
Order By: Relevance
“…Shifting the Asp from the C‐ to the N‐terminus was shown to invert the conformation from a parallel to an antiparallel β‐sheet 20. Similarly, both the D2I3 and DI3D peptides contain charged Asp species situated at the termini of the sequence with regions of three repeat Ile residues.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…Shifting the Asp from the C‐ to the N‐terminus was shown to invert the conformation from a parallel to an antiparallel β‐sheet 20. Similarly, both the D2I3 and DI3D peptides contain charged Asp species situated at the termini of the sequence with regions of three repeat Ile residues.…”
mentioning
confidence: 98%
“…The native tripeptide sequences discovered to self‐assemble into stable hydrogels have contained aromatic amino acids such as the KYF and DFY motifs 3, 20. Oligopeptides that consist of amino acids with aliphatic side chains have received less attention 21, 22.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Being easily accessible via solid phase synthesis, peptides are becoming important building blocks for generating supramolecular assemblies for a wide range of applications such as antibacterial agent, [18] self-assembly with non-covalent interaction, [19] conjugating with anticancer drug, [20] and sequence control for generating melanin-like color. [21] Therefore, the use of enzyme reaction for controlling the secondary structure of peptides will contribute to design more sophisticated and intelligent soft biomaterials for a wide range of applications.…”
mentioning
confidence: 99%
“…Ulijn and co-workers demonstrated that the melanin-mimetic materials with tunable coloration ability were synthesized by the self-assembly of tyrosine-containing tripeptides followed by oxidative polymerization using tyrosinase. [115] The polypeptides obtained by chemoenzymatic polymerization possess a free amino group at their N-termini and an ester group at their C-termini. These structural features are useful for further functionalization, including block copoly mer synthesis.…”
Section: Combination With Chemical Modificationsmentioning
confidence: 99%